Effects of taro [Colocasia esculenta (L.) Schott] slices on nutritional quality, sensory quality, and shelf life of Chinese pickled and steamed pork belly - Quan, Qinguo; Zhang, Yexuan; Nawaz, Asad; Feng, Luya; Qin, Zuodong (Frontiers in Nutrition, 2023)
This study aimed to investigate the influence of different ratios of taro slices (TS) on the nutritional quality, sensory quality, and shelf life of Chinese pickled and steamed pork belly (CPSPB). The study examined various aspects of CPSPB, including its proximate components, fat oxidation, fatty acid composition, protein hydrolysis, oxidation reaction, and induction period (IP). Additionally, the sensory quality and texture analysis were compared simultaneously. The results showed that the addition of TS to CPSPB significantly improved water and lipid loss (p < 0.05), increased the unsaturated/saturated ratio of fatty acids, and reduced lipid and protein oxidation. Additionally, the incorporation of TS extended the IP and enhanced the shelf life of CPSPB. Particularly, the addition of a specific amount of TS (60%) to CPSPB resulted in the highest organoleptic quality. Therefore, these results emphasize the positive impact of TS on the overall quality of CPSPB, highlighting its potential to enhance the nutritional value, sensory attributes, and shelf life.